PERLINDUNGAN HUKUM TERHADAP TANAH PERTANIAN ATAS ALIH FUNGSI MENJADI TANAH PERUMAHAN DAN INDUSTRI - Munir, Saiful (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2020)
The modernization paradigm that has been developing is that developed countries are industrial countries. Thus, if Indonesia turns into a modern country, it must change itself from an agricultural country to an industrial country. The regional government and the apparatus of the related institutions in the effort to realize the protection of sustainable food land are still limited to carrying out their main tasks and functions as outlined in the regional regulation, there are no other sociological efforts aimed at realizing sustainable agricultural land protection. This research was conducted to determine the product of government law in reducing the conversion of agricultural land into residential and industrial land. This is to determine the form of legal protection due to the conversion of agricultural land into residential and industrial land. The research carried out is a normative juridical legal research, which is a type of research that will examine the regulations, both legislation and other regulations under the law, which have a relationship with the issues the author is examining. In conducting research, the authors use several approaches, including a statutory approach (statue approach), a conceptual approach (conceptual approach), a historical approach (historical approach) and a comparative approach (comparative approach). The transfer of the function of agricultural land to non-agricultural in various regions in Indonesia is mostly carried out by the land owner itself and is influenced by other factors both internal and external as well as government policy factors.